Skills, social mobility, and the support for the welfare state - Johannes Rincke; Robert Schwager (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2005)
Many welfare schemes discourage low skilled individuals from working. In the same time, there is widespread support for the welfare state among the highly educated. We suggest a model which explains these seemingly contrasting observations. In our approach, intergenerational social mobility is conditional on labour market participation of the parents. Such mobility increases the supply of high skilled labour in the next generation. To protect their children from the associated fall in wages, middle class parents have an incentive to induce unemployment among low skilled parents, and therefore vote for a social transfer.
Keywords: H53; I38; D72; 330; political preferences; unemployment; voting; social mobility; welfare state